2016
DOI: 10.1016/j.virol.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of pathology in ferrets infected by H9N2 avian influenza viruses with different genomic features

Abstract: H9N2 avian influenza virus circulates widely in poultry and has been responsible for sporadic human infections in several regions. Few studies have been conducted on the pathogenicity of H9N2 AIV isolates that have different genomic features. We compared the pathology induced by a novel reassortant H9N2 virus and two currently circulating H9N2 viruses that have different genomic features in ferrets. The results showed that the three viruses can induce infections with various amounts of viral shedding in ferret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Ferrets inoculated with field H9N2 isolates show mild clinical signs with the infection confined mostly to the upper respiratory tract (Wan et al 2008). In contrast, ferrets inoculated with H9Nx avian/ mammalian reassortants produce clinical signs and lung pathology associated with moderate to severe broncho-interstitial pneumonia, consistent with macrophages, lymphocyte and neutrophil infiltrations, alveolar edema, and rupture (Wan et al 2008;Sorrell et al 2009;Kimble et al 2011Kimble et al , 2014Gao et al 2016). Recently, tree shrews have been proposed as an alternative to ferret and nonhuman primate models, being evolutionarily closer to humans.…”
Section: Clinical Signs Pathology and Interspecies Transmissionmentioning
confidence: 99%
“…Ferrets inoculated with field H9N2 isolates show mild clinical signs with the infection confined mostly to the upper respiratory tract (Wan et al 2008). In contrast, ferrets inoculated with H9Nx avian/ mammalian reassortants produce clinical signs and lung pathology associated with moderate to severe broncho-interstitial pneumonia, consistent with macrophages, lymphocyte and neutrophil infiltrations, alveolar edema, and rupture (Wan et al 2008;Sorrell et al 2009;Kimble et al 2011Kimble et al , 2014Gao et al 2016). Recently, tree shrews have been proposed as an alternative to ferret and nonhuman primate models, being evolutionarily closer to humans.…”
Section: Clinical Signs Pathology and Interspecies Transmissionmentioning
confidence: 99%
“…Experimental studies also have shown that domestic cats and dogs are susceptible to H9N2 AIVs [101,102] , thus may serve as host species contributing to the adaptation of H9N2 viruses in mammals. In ferrets, H9N2 infection results in high replication and efficient transmission by direct contact [103] and leads to mild to moderate lesions in lung tissue when infected by H9N2 AIVs with different genomic features [104] . In guinea-pigs, the H9N2 virus was restricted to the respiratory system and shed at high titers through the nasal tracts [105] .…”
Section: Pathogenicity Of the H9n2 Aivsmentioning
confidence: 99%
“…Since 2010, two subtypes of influenza have circulated in Egyptian poultry and wild birds, H5N1 and H9N2 [4]. H9N2, while less deadly than H5N1, can and does infect humans, and is also considered a pandemic candidate [23].…”
Section: Motivation and Objectivesmentioning
confidence: 99%
“…can cause serious illness, and recent isolates of avian H9N2 have shown mutations which improve binding with human cells [23].…”
Section: The Influenza Virusmentioning
confidence: 99%
See 1 more Smart Citation